INTRAPRENEURSHIP OF MIDDLE-LEVEL MANAGERS: HOW TO TRIGGER THEIR ACHIEVEMENT MOTIVATION? - Elkana Timotius (Jurnal Manajemen dan Kewirausahaan, 2023)
This research aimed to find a way to trigger the achievement motivation of middle-level managers as intrapreneurs. It was quantitative research with data collected from 41 store managers in a national bicycle retail chain in Indonesia through 32-Likert scale questions. Path analysis measures the effect of three independent variables and one intervening variable on a dependent variable. The findings indicated that the achievement motivation of a middle-level manager was directly affected by the reward system and job satisfaction. However, they need management support to become intrapreneurs in the retail business. Management support had a significant direct effect on job satisfaction and a significant indirect and direct effect on achievement motivation. The work environment, reward system, and management support simultaneously directly affected achievement motivation. In short, these findings encourage companies to focus on management support to trigger the achievement motivation of middle-level managers. Job satisfaction, reward system, and work environment also contribute to reaching this objective consecutively.